Cardiometabolic Health Disparities in Native Hawaiians and Other Pacific Islanders - Mau, Marjorie K. (2009)
Elimination of health disparities in the United States is a national health priority. Cardiovascular disease, diabetes, and obesity are key features of what is now referred to as the “cardiometabolic syndrome,” which disproportionately affects racial/ethnic minority populations, including Native Hawaiians and other Pacific Islanders (NHOPI). Few studies have adequately characterized the cardiometabolic syndrome in high-risk populations such as NHOPI. The authors systematically assessed the existing literature on cardiometabolic disorders among NHOPI to understand the best approaches to eliminating cardiometabolic health disparities in this population. Articles were identified from database searches performed in PubMed and MEDLINE from January 1998 to December 2008; 43 studies were included in the review. There is growing confirmatory evidence that NHOPI are one of the highest-risk populations for cardiometabolic diseases in the United States. Most studies found increased prevalences of diabetes, obesity, and cardiovascular risk factors among NHOPI. The few experimental intervention studies found positive results. Methodological issues included small sample sizes, sample bias, inappropriate racial/ethnic aggregation of NHOPI with Asians, and a limited number of intervention studies. Significant gaps remain in the understanding of cardiometabolic health disparities among NHOPI in the United States. More experimental intervention studies are needed to examine promising approaches to reversing the rising tide of cardiometabolic health disparities in NHOPI.